A propensity-score matched analysis on the impact of postoperative atrial fibrillation on the early and late outcomes after concomitant aortic valve replacement and coronary artery bypass graft surgery - Saxena, A.; Shi, W.; Paramanathan, A.; Herle, P.; Dinh, D.; Smith, J.; Reid, Christopher; Shardey, G.; Newcomb, A. (Lippincott Williams and Wilkins, 2014)
Background: Postoperative atrial fibrillation (POAF) is a known complication of cardiac surgery. There is a paucity of data on the effects of POAF on short-term and long-term outcomes after concomitant aortic valve replacement and coronary artery bypass grafting (AVR-CABG ). Methods: We retrospectively reviewed data on patients without preexisting arrhythmia who underwent isolated first-time AVR-CABG between June 2001 and December 2009 using the Australasian Society of Cardiac and Thoracic Surgeons National Cardiac Surgery Database Program. Preoperative characteristics, early postoperative outcomes and late survival were compared between patients who developed POAF and those who did not. Propensity score matching was performed to account for the differences between the two groups. Results: Isolated AVR-CABG surgery was performed in 2028 patients without preexisting arrhythmias at 18 Australian institutions, of whom 894 (44.1%) developed POAF. POAF patients were generally older (mean age, 75 vs. 73 years, P < 0.001). From the initial study population, 715 propensity-matched patient-pairs were derived; the overall matching rate was 80.0%. In the matched groups, 30-day mortality was similar in both groups (3.5 vs. 2.1%, P = 0.16). Patients with POAF, however, were more likely to develop perioperative complications, including new renal failure, prolonged ventilation (>24 h), multisystem failure and readmission within 30 days of surgery (all P < 0.05). Patients with POAF also had a significantly greater length of hospital stay (P < 0.001). Seven-year survival was not significantly different between the two groups (72 vs. 75%, P = 0.11). Conclusion: POAF was not associated with an increased risk of early or late mortality. It is, however, associated with poorer perioperative outcomes. It is important to evaluate potential treatment strategies for POAF.